The Perspective of Students Towards Soft Skills in English Language Learning at Souphanouvong University - BANDASACK, Bouaphanh; KEOBOUALAPHETH, Soulideth; HUNGSAVATH, Thongkham (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objective of this study was to examine students' perspectives on the role of soft skills in English language learning at Souphanouvong University. A quantitative method was employed to achieve the objective. The primary research instrument utilized in this study was a structured questionnaire using a 5-point Likert scale and encompassing four key soft skills: communication skills, collaboration skills, creative thinking skills, and critical thinking/problem-solving skills. The questionnaires included 43 items in total. They were distributed to the population of students enrolled in the General English Language Program at the Faculty of Languages, Souphanouvong University, for a total of 109 participants. The data were analyzed using the Statistical Package for the Social Sciences (SPSS, version 26) program to calculate percentages, mean values, and standard deviation. The results showed that students perceived soft skills as highly important in English language learning. Among the four soft skills assessed, communication skills were ranked the highest, with mean = 4.19 and SD = 0.47. This was followed by creative thinking skills with mean = 3.96 and SD = 0.50, collaboration skills with mean = 3.95 and SD = 0.47, and critical thinking/problem-solving skills with mean = 3.83 and SD = 0.53. Based on these results, students’ perspective toward soft skills in English language learning is important and considered helpful in their learning.